Sustainable pink ink synthesis from calcium rich/eggshell waste: Chromium tin pink sphene - Toy, Emre; Unluturk, Kumru Karaman; Yesilci, Emine; Aslan, Emre; Karaahmet, Oguz; Grijalbo, Alejandro; Cicek, Bugra (ELSEVIER, 2024)
The chromium-doped tin sphene or malayaite (Ca(Sn,Cr)SiO5, PR233) was synthesized by solid-state reaction method at temperatures between 1300 and 1500 degrees C. Two different pigments were obtained according to the chemical formula CaSn(1-x)SiCrxO5 +/-delta (x = 0.01 and 0.03). Eggshell, calcium-rich wastes (CRW), were utilized as raw material. The eggshell was only washed and milled. In the pigment reactant formula, more than 30% by weight of CRW was used. Pigments were milled by a planetary ball mill with zirconium oxide equipment. The pigments obtained were used as glaze colorants and inks by reducing the particles to micro and nano sizes, respectively. The Dv(90) of pigments milled for glaze application is 7.19-7.98 mu m, while it is 660-678 nm for ink application. Micron-sized pigments were mixed with transparent glaze and applied to the engobe-coated ceramic tile with a pool-type film applicator. The inks were applied to engobe-coated and transparent glazed ceramics through the screen printing method. After glaze and ink application, ceramic tiles were fired at 1130 degrees C. When the color values of glaze application are examined, the values for L*, a* and b* are between 48.9 and 63.8, 18.4-23.5, 1.2-4.6, respectively. In the Ink application, L*, a* and b* are 71.0-81.2, 21.8-12.7 and 0.9-2.8, respectively. Characterization was performed using various devices such as X-ray diffraction (XRD), X-ray fluorescence (XRF), field emission-scanning electron microscopy (FE-SEM), and spectrophotometer. The conducted studies revealed that the calcium requirement for Ca(Sn,Cr)SiO5 pigment was entirely met using CRW, and a ceramic ink suitable for inkjet applications was successfully obtained.
Keywords: Eggshell; Ink-jet; Pigment; Sustainability; Ceramic glaze; Malayaite; Calcium source; CERAMIC PIGMENTS; EGGSHELL WASTE; GLASSES; SPECTROSCOPY; PRODUCTS; COLOR; RED; Science & Technology - Other Topics; Materials Science